1996
DOI: 10.1103/physrevb.54.12151
|View full text |Cite
|
Sign up to set email alerts
|

Transport of 29cm1phonons in hydrogenated amorphous silicon

Abstract: The scattering of 29 cm Ϫ1 phonons in hydrogenated amorphous silicon ͑a-Si:H͒ at 2 K is investigated by means of optically generated heat pulses and the ruby phonon detector. The transport is shown to be governed by elastic spatial diffusion and a diffusion coefficient of ϳ1 cm 2 /s. Resonant scattering by soft oscillators, as well as Rayleigh scattering by microvoids or by the disordered network itself account for the experimental findings. In optically excited a-Si:H, the transmission of 29 cm Ϫ1 phonons is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Also in these experiments we found that the phonon dynamics in a-nc-Si:H is markedly different from that in a-Si:H. The outcome of the transport experiments on a-Si:H is consistent with the results published by Scholten et al, who extensively studied the scattering of 29-cm Ϫ1 phonons in a-Si:H. 11 They showed that in a-Si:H the transport of 29-cm Ϫ1 phonons is governed by elastic spatial diffusion with a diffusion coefficient of ϳ1 cm 2 /s. Encouraged by their analysis, we try to explain the results of the phonon transport measurements on a-nc-Si:H in terms of an elastic diffusion model.…”
Section: B Long-lasting Phonon-induced Luminescence Signalssupporting
confidence: 91%
See 4 more Smart Citations
“…Also in these experiments we found that the phonon dynamics in a-nc-Si:H is markedly different from that in a-Si:H. The outcome of the transport experiments on a-Si:H is consistent with the results published by Scholten et al, who extensively studied the scattering of 29-cm Ϫ1 phonons in a-Si:H. 11 They showed that in a-Si:H the transport of 29-cm Ϫ1 phonons is governed by elastic spatial diffusion with a diffusion coefficient of ϳ1 cm 2 /s. Encouraged by their analysis, we try to explain the results of the phonon transport measurements on a-nc-Si:H in terms of an elastic diffusion model.…”
Section: B Long-lasting Phonon-induced Luminescence Signalssupporting
confidence: 91%
“…On the other hand, the trailing edge decays on the same ϳ50-ns time scale for different excitation powers, i.e., much faster than the decay of the R 2 /R 1 signals presented above for a-nc-Si:H for configuration ͑1͒. These observations are in agreement with the results reported for a-Si:H by Scholten et al 11 and are therefore not shown.…”
Section: B Experiments With the Ruby Phonon Detectorsupporting
confidence: 91%
See 3 more Smart Citations